2020
DOI: 10.1007/s10623-020-00815-x
|View full text |Cite
|
Sign up to set email alerts
|

Steiner systems and configurations of points

Abstract: The aim of this paper is to make a connection between design theory and algebraic geometry/commutative algebra. In particular, given any Steiner System S(t, n, v) we associate two ideals, in a suitable polynomial ring, defining a Steiner configuration of points and its Complement. We focus on the latter, studying its homological invariants, such as Hilbert Function and Betti numbers. We also study symbolic and regular powers associated to the ideal defining a Complement of a Steiner configuration of points, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…We also point out that the two above preprints [21,22] do not compute the Waldschmidt constant exactly for any class of ideals, they study lower bounds for the Waldschmidt constant. Furthermore, as in [1] the authors found the exact value of the Waldschmidt constant for the Complement of a Steiner configurations of points, then Chudnovsky and Demailly's Conjectures easily follow for our class of ideals (see Section 3).…”
Section: Conjecture 3 (Stable Harbourne Conjecturementioning
confidence: 52%
See 4 more Smart Citations
“…We also point out that the two above preprints [21,22] do not compute the Waldschmidt constant exactly for any class of ideals, they study lower bounds for the Waldschmidt constant. Furthermore, as in [1] the authors found the exact value of the Waldschmidt constant for the Complement of a Steiner configurations of points, then Chudnovsky and Demailly's Conjectures easily follow for our class of ideals (see Section 3).…”
Section: Conjecture 3 (Stable Harbourne Conjecturementioning
confidence: 52%
“…We will focus on the Containment problem, and we will show that the Stable Harbourne Conjecture and the Stable Harbourne-Huneke Conjecture hold for the defining ideal of a Complement of a Steiner configuration of points in P n k := P n . As pointed out in Remarks 2.5 and 2.6 in [1] in the language of Algebraic Geometry/Commutative Algebra, Steiner configurations of points and their Complement are special subsets of star configurations.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations